2004
DOI: 10.1111/j.1540-6210.2004.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Implementing the Government Performance and Results Act: Top‐Down Direction for Bottom‐Up Implementation

Abstract: Research on the implementation of the Government Performance and Results Act generally has not considered how the strategic plan, annual performance plan, and annual performance report are produced and used. Are the documents good decision and management tools, as the act intends, or are agencies internalizing them to meet the unique needs of their organization? Interviews with representatives of 14 cabinet-level federal agencies suggest that implementation of the act is not standardized. Instead, it is influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 16 publications
1
49
0
2
Order By: Relevance
“…Further, by holding public agencies accountable for performance, policymakers are able to get more "bang for the buck" by spending less money on programs that do not work and more on those that do. While performance budgeting has become ubiquitous at all levels of government in America over the last fifteen years (Kettl 2000;Melkers and Willoughby 1998;Moynihan 2006a), empirical research has generally found only limited evidence that performance information has a meaningful impact on budget decisions, particularly at the state and federal levels of government Lewis 2006b, 2006a;Joyce 1999;Long and Franklin 2004;Moynihan 2006b;Radin 2000). Why have policymakers been so apt to adopt performance mechanisms if they do not use the information that these systems generate ?…”
Section: Accountability and The Performance Movementmentioning
confidence: 99%
“…Further, by holding public agencies accountable for performance, policymakers are able to get more "bang for the buck" by spending less money on programs that do not work and more on those that do. While performance budgeting has become ubiquitous at all levels of government in America over the last fifteen years (Kettl 2000;Melkers and Willoughby 1998;Moynihan 2006a), empirical research has generally found only limited evidence that performance information has a meaningful impact on budget decisions, particularly at the state and federal levels of government Lewis 2006b, 2006a;Joyce 1999;Long and Franklin 2004;Moynihan 2006b;Radin 2000). Why have policymakers been so apt to adopt performance mechanisms if they do not use the information that these systems generate ?…”
Section: Accountability and The Performance Movementmentioning
confidence: 99%
“…What was missing in this literature is the motivations and behaviors of the local agents for implementation. The second wave of policy implementation scholars have thus focused on the bottom-up strategies in policy implementation, with explicit focus on the motivations of the street-level bureaucrats [16][17][18]. The development and application of performance management across government entities represents efforts to integrate the top-down approach with the bottom up approach to policy implementation [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One aspect of NPM (Azuma, 2005) has been a focus on improved performance, and Holmes (1992) described a recurring theme of public sector reform involving both improving performance and enhancing accountability. Some authors argue that the implementation of performance measures has often been the critical link that impacts the success or failure of government programmes (Long and Franklin, 2004).…”
Section: The Nature Of Performance Auditmentioning
confidence: 99%